Evaluating 5G coverage in 3D scenarios under configurable antenna beam patterns - Jesus, Francisco (2022)
Active Antenna Systems (AASs) play a key role in the performance of 5 th Generation (5G) networks as they enable the use of Massive Multiple-Input Multiple-Output (mMIMO) and directional beamforming. Besides, AASs can be configured with distinct broadcast beams configurations. In this work, the coverage provided by the broadcast beam configurations of a real AAS is evaluated. A 3-Dimensional (3D) configurable synthetic scenario was proposed to evaluate the resulting 5G coverage from all the possible antenna beam configurations. This analysis revealed that beam configurations with several horizontal beams and one vertical are recommended for urban macro deployments. Moreover, it was demonstrated that the percentage of covered area in a real scenario is approximated by an equivalent synthetic scenario with a Pearson correlation of 0.98. The synthetic scenario has the advantage of not requiring 3D building databases. Finally, an interference analysis in multi-site real scenarios was conducted, where it was verified that some antenna configurations introduce excessive interference for the level of coverage provided.